Pengaruh Alih Baring Selama Fototerapi Terhadap Perubahan Kadar Bilirubin Pada Ikterus Neonatorum di Ruang HCU Neonatus RSUD Dr. Moewardi - Nur Widya Wikanthiningtyas; Sri Mulyanti ((JKG) Jurnal Keperawatan Global, 2016)
Abstrack: Position Exchange Is Right Oblique, Supine, Left Oblique, And Prone In Phototherapy. Icterus neonatorum is neonatus condition with high bilirubine levels. Objective to determine the effect position exchange in phototherapy to the bilirubine levels in icterus neonatorum in HCU Neonatus Dr. Moewardi General Hospital. Researchers used a quasy experimental design pre- post test one group. Researcher used a sample of 25 neonatus. Analysis of differences in pre and post bilirubine levels of phototherapy. The collected data was analyzed by using paired t test. Retrieved from 25 respondents, it is the majority age of icterus neonatorum is 4 days (28,6%) and the majority of the male gender with a percentage of 52 %. Research results obtained that effect position exchange in phototeraphy to the bilirubine levels in icterus neonatorum in HCU Neonatus Dr. Moewardi General Hospital with p =0.00. Based on the analysis it can be concluded that there is a significant the effect between position exchange in phototherapy to the bilirubine level in icterus neonatorum in HCU Neonatus Dr. Moewardi General Hospital.